Understanding Factors That Influence the Recruitment and Retention of Male Occupational Therapists in Aotearoa New Zealand - Leadley, Simon; Broman, Patrick; Mills, Darren; Sutton, Daniel (Wiley, 2026)
Low levels of recruitment and retention of men in the occupational therapy profession have been a long-standing issue. This study examined the recruitment and retention of men in occupational therapy in Aotearoa New Zealand, with the aim to better understand what factors have been influencing this issue. The study employed an interpretive descriptive qualitative methodology. Focus groups were conducted with male occupational therapy students and practitioners. A thematic analysis approach was utilised. Strategies to ensure rigour and address cultural and ethical considerations were used throughout study. Two key themes emerged: Identity and Diversity. The first theme, Identity, highlighted limited public awareness about occupational therapy and its altruistic and pragmatic nature. It also drew attention to its perception as a predominantly female and white profession. These factors were identified as barriers to attracting and retaining men. Participants reflected on the transformative potential of occupational therapy, its hands-on approach to problem-solving, and the need for better promotion of the profession to appeal to men. The second theme, Diversity, addressed the lack of gender, ethnic, and cultural representation within occupational therapy. It also highlighted the advantages that greater diversity brings to practice. Participants emphasised that diverse perspectives are crucial for meeting the needs of Aotearoa New Zealand’s population. The wide range of roles and career opportunities within occupational therapy were also identified as factors that could encourage more men into the profession.
Keywords: 1103 Clinical Sciences; Rehabilitation; 4201 Allied health and rehabilitation science; men; occupational therapy; recruitment; retention